Migraine and benign paroxysmal positional vertigo: An outcome study of 476 patients - (:unkn) unknown (Medquest Communications LLC, 2004)
To investigate whether migraine is more common in patients with benign paroxysmal positional vertigo (BPPV) than in the general population, the author conducted a retrospective study of 476 patients with BPPV seen over 12 years at a tertiary referral center. Records of patients with a confirmed diagnosis of BPPV followed for 1 to 7 years were reviewed The typical history of BPPV and the characteristic torsional positional nystagmus were identified in all patients. A modified Epley maneuver was performed for all patients with posterior semicircular canal BPPV, with a 98% success rate. The survey consisted of detailed patient questionnaires and vestibular tests. Migraine and motion sickness were three times more common in patients with BPPV than in the general population. A family history of migraine (58.4%) and vertigo (44.9%) was also more common in patients than in a control group.